Method for preparing particles, porous particles, and use of porous particles
By manufacturing antibacterial coating particles on drinking water filter materials, the problem of difficulty in removing multiple pollutants in drinking water at the same time in the prior art is solved, and efficient and low-cost water quality improvement effect is achieved.
Patent Information
- Application Number
- JP2024231919
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-03-15
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2040-03-13
AI Technical Summary
The prior art is difficult to efficiently remove heavy metals, microcontaminants, bacteria and other harmful substances in drinking water at the same time. The commonly used reverse concentration technology consumes high energy and has low water yield, and traditional filter materials are prone to microbial contamination and water leakage.
A method of making antibacterial coating particles is adopted, which comprises using polyamines, crosslinking agents and organic or inorganic carrier materials, by adding polyamines to an aqueous suspension of the carrier material and processing at a temperature below 10°C, and then crosslinking the organic polyamines in the pores of the carrier material to form an antibacterial coating.
It has achieved efficient removal of various pollutants such as heavy metals, micropollutants, bacteria in drinking water, reduced production costs and energy consumption, and improved the antibacterial performance and stability of the filter material.
Smart Images

Figure 2025066729000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the detection of heavy metals, elemental acid or elemental acid anions, as well as certain microcontaminants. For the manufacture of adsorption resins for the removal of substances and bacteria from aqueous solutions, commercial ion exchangers or by a pure outer coating of the porous polymer particles with amino group-containing polymers. The process involves complete coating and subsequent modification of the polymer with functionalizing ligands. It provides a service that
[0002] According to a 2015 report by the World Economic Forum, the water crisis will affect the entire world population. It has been defined as the world's number one risk to human health.
[0003] In addition, the World Health Organization (WHO) and UNICEF estimate that there are currently 600 million 63 million people lack access to clean drinking water and 2.4 billion have inadequate water resources This is emphasized as of 2015.
[0004] Such situations include continued population growth, climate change, or the loss of water resources due to global warming. There are several reasons for this, including a decrease in the number of toxic substances in the water supply, and an increase in polluted water sources contaminated by industrial waste. Therefore, improving drinking water quality and reducing water pollution is crucial.
[0005] Drinking water sources can become contaminated by a variety of contaminants. These contaminants include chemicals, bacteria, micro-pollutants, and heavy metals. These contaminants have many health benefits. For this reason, it needs to be removed from the water before drinking.
[0006] There are several methods by which contaminants can be removed to obtain safe, clean drinking water. The most common technique is mechanical filtration, which can be performed using a variety of techniques or processes. This has been achieved by using filters, membranes, etc. with a specific pore size smaller than the contaminant. It is essential to filter out the staining material.
[0007] Reverse osmosis is one such filtration method, and most of the water filtered (about 90%) is It is disposed of as waste and has high operating costs (power demand, etc.). Currently, the world's water sources are drying up. Considering the current situation, it is important to develop cost-effective and water-saving technologies for drinking water filtration. Development is important.
[0008] No single commercially available technology can target the full range of potential contaminants. It is now clear that, for example, it can remove chlorine from water. This also applies to resins supplied by instrAction GmbH. As a result, known purification techniques (e.g., activated carbon for "chlorine") and the removal of heavy metals, elemental acids or elemental acids Intelligently and innovatively combines innovative adsorption resins for the removal of anions, micropollutants, and bacteria. There is a demand for new combinations.
[0009] Productivity is determined by the sorption of contaminants in a bed of adsorbent resin with a known contaminant profile and desired removal rate. This is essentially determined by the required residence time. For example, small particles are This is favorable since it provides a shorter diffusion path, but on the other hand it increases the counter pressure in an undesirable manner. It is difficult to stably and easily pack only large particles into a small bed, so larger particles On the other hand, larger particles have longer diffusion paths. Therefore, longer residence times are likely to be required.
[0010] In terms of competing technologies on the market, reverse osmosis (RO) is the most widely used technology. Grand View Research (Market Research According to a 2017 market study by the US Water and Energy Research Institute (USA) (Reports & Consulting), reverse osmosis is the largest market for domestic drinking water treatment. It has a market share of approximately 44% in the field. In 2016, it sold approximately 210 million 0 million units were sold.
[0011] The major drawback of RO modules is that the yield is very low. About 10-20% is actually purified and delivered to the customer. The pumps used for the RO system consume electricity, and the water quality is also a problem. To provide pure water that does not contain essential salts, essential salts (e.g. calcium and magnesium) are reconstituted. It must be added once.
[0012] The drawback of very high energy consumption is common to all distillation processes. As with osmosis, health-promoting compounds are also removed, resulting in long-term This produces unsuitable distilled water and requires the re-addition of key ingredients such as magnesium salts at a later stage. It is necessary to do so.
[0013] Water purifiers that combine multiple filtration technologies in separate units / cartridges are It requires complex piping with valves or connectors, which are prone to failure and leaks. Furthermore, the joints are places where bacteria and other microorganisms can easily grow due to the flow of water. This is a useful point.
[0014] Known filtration media that are commercially available are, for example, activated carbon, which has straight through channels. as a packed bed of particles in a cartridge or in a compressed hollow cylinder with radial through-flows. It is used as a datum.
[0015] Ion exchange resins also bind heavy metals in competition with calcium and magnesium. Unreliable due to binding of heavy metals or close to exhausting the full capacity of ion exchange At the same time, heavy metals are washed out of the resin in a concentrated form. If present, they will reach a state of depletion very quickly. From this point on, heavy metals will not be removed. On the contrary, the heavy metal ions already immobilized on the ion exchanger are dissolved in excess. Since the sodium ions are replaced by alkaline earth metals, a relatively small amount is eluted. The sodium in drinking water is released into the water by the ion exchanger. This is increasingly viewed with skepticism due to its association with baby food and cardiovascular disease. In addition to heavy metals, elements such as selenide, selenate, arsenide, and arsenate The elemental salt anions, as well as the elemental salt anions, have raised concerns about the health of consumers and water users. It is thought that.
[0016] The resulting problem was to develop a method for purifying water reliably and with a high yield while simultaneously removing bacteria. To produce adsorbents for metals, elemental acid anions and elemental acid salt anions reliably and inexpensively. The purpose is to create Summary of the Invention
[0017] This object is achieved by a method for producing antimicrobially coated particles, The manufacturing method includes the following steps: (a) a polyamine, a crosslinker, and a porous particulate organic or inorganic support material; to coat the inorganic support material with the polyamine, feeding into a mixer at a temperature of 10°C or less; (b) removing water whilst crosslinking the organic polymer within the pores of said inorganic support material.
[0018] Within the meaning of the present invention, it is preferred to repeat steps a) and b) at least once. I wish.
[0019] In a preferred embodiment of the method, the crosslinking is carried out in a stirred reactor.
[0020] It has proven advantageous to use the polyamines in a non-desalted state.
[0021] The organic carrier polymer is preferably polystyrene.
[0022] In a further embodiment, the organic carrier polymer is coated with a polymer only on its outer surface. It is a coated strong or weak anion exchanger. Organic polymers that have carboxylic acid groups are called strong anion exchangers. It is a polymer having the formula:
[0023] In a further embodiment of the invention, the organic polymer is polystyrene, polymethacrylate The polyacrylate is selected from the group consisting of polyacrylates, polyvinyl chloride, and polyacrylates.
[0024] The polymer (polymer compound) is made of silica gel and hydroxyapatite. The inorganic polymer may be an inorganic polymer (inorganic polymer compound) selected from the following.
[0025] Furthermore, the polyamine is preferably polyvinylamine.
[0026] A further object of the present invention are antimicrobial porous particles, preferably of crosslinked polyamines, as described above. It can be obtained or produced according to the methods described above.
[0027] Yet another object of the present invention is to provide a heavy metal-adsorbing porous particle produced according to the above-mentioned method. It is.
[0028] It is yet another object of the present invention to provide a method for the preparation of cations of elements such as selenides, selenates, arsenides, and arsenates. The method according to the present invention further comprises the steps of: The particles can be obtained or produced according to the method of the present invention.
[0029] Groups 15 and 16 of the periodic table (formerly main groups 5 and 6) that contain four oxygen atoms ) are compounds derived from elemental acids or elemental acid anions (Elementsauren bzw. Anionen der Ele mentsauren), and thus, for example, H3AsO4 or AsO4 3- , H3SeO4 or SeO4 3- There is.
[0030] Compounds from groups 15 and 16 of the periodic table that have three oxygen atoms are called elemental hypochlorites or Elemental anions (anions of elemental acids) Thus, for example, H3AsO3 or AsO3 3- , H3SeO3 or SeO3 3- There is.
[0031] Like activated carbon, ion exchangers also reduce the risk of microbial contamination and biofilm formation on surfaces. Therefore, ultimately, even drinking water with low microbial contamination is considered to be a so-called “purified water.” After "immobilization," the sample will contain more bacteria than before.
[0032] The challenge this creates is how to improve the potable water quality without significantly reducing the capacity of the ion exchanger. The object of the present invention is to provide an ion exchanger, such as that used in softening the skin, with an antimicrobial surface.
[0033] At the same time, potentially toxic micropollutants have increasingly become the focus of public and expert attention. It is becoming.
[0034] This is especially true for perfluorosurfactants (perfluorooctanoic acid, This is true for surfactants such as benzenesulfonic acids, which are not biodegradable or are only slightly biodegradable. It does not decompose and is therefore highly persistent ("Sachstandsbericht ADONA und perfurorient e Substanzen” (“Assessment report ADONA and perfluorinated substances”), (Source: Bavarian State Office for Health and Food Safety).
[0035] There are many highly inefficient and expensive methods for removing perfluorosurfactants from drinking water. For example, activated carbon has a very low capacity for this type of pollutant. Filtration or other methods that provide clean drinking water but also contain perfluorosurfactants These include membrane processes that produce large volumes of wastewater in concentrated form. It is either disposed of in a suitable manner (typically by incineration) or reintroduced into the wastewater. To the best of our knowledge, there are currently no selective adsorbents with high throughput for perfluorosurfactants. do not have.
[0036] The challenge that this presents is that in addition to heavy metals and bacteria, perfluorosurfactants are also ingested. The object of the present invention is to improve and further develop known resins so that they can be removed from drinking water.
[0037] Heavy metals from drinking water (WO2015EP01754, WO2016EP78787) and Resins capable of removing bacteria (DE102017007273.6) are known. In the method, the amino polymer is immobilized on an associated support and reacted with a bifunctional crosslinker to form a stable These resins therefore have a significant role in drinking water purification plants. as a filter for heavy metals in the sludge and in the final stage of the purification cascade by the orthogonal method It is suitable for both as a "police filter" to remove heavy metals.
[0038] The first step in resin production is the preparation of the desired coating polymer, polyvinylformamide. was synthesized and hydrolyzed with aqueous sodium hydroxide in a polymer-like reaction to obtain poly Vinylamine (PVAm) is then prepared. This is followed by a time-consuming and costly cross-flow The reagents and the separated product are removed by filtration. The desalted polymer solution is then In a second step, it is used to coat the carrier material.
[0039] Environmental issues (reduction of energy consumption and wastewater volume) and the demand for drinking water purification systems In essence, there is a need to simplify the manufacturing process to reduce costs and conserve resources.
[0040] So far, the so-called MetCap ( It was only known that the granules ( DE102017007273.6). The preparation method and activity detection method are described in DE1020170 No. 07273.6, which discloses silica gel particles made of non-desalting polymers. (as a template) coating and subsequent dissolution of the inorganic carrier and its antibacterial activity It is explained.
[0041] Similar activity has not been previously known for particles based on organic carriers, e.g. polystyrene. Now, surprisingly, this activity has been demonstrated in a new process The resin will be based on polystyrene. Polystyrene is usually very biocompatible. This finding was surprising, as the films tend to form and do not remove bacteria at all. Apparently, the new coating prevents bacteria from growing on polystyrene surfaces. This ensures that they do not multiply but rather are excluded from the matrix (here, drinking water).
[0042] The various problems resulting from the above reasons have led to the need to improve and further develop known resins with the aim of: The aim is to develop this into a [Brief description of the drawings]
[0043] [Figure 1] FIG. 1 is glycidyl 2,2,3,3,4,4,5,5-octafluoropentyl ether. [Diagram 2] FIG. 2 shows one of two structural isomers of the adsorbate of a perfluorosurfactant (R=polymer). [Diagram 3] FIG. 3 is the chromatographic breakthrough profile of PV 150772 (instrAction resin batch: batch number ND 150201); breakthrough does not occur until approximately 900 minutes, or 220 mg of perfluorooctanoic acid per mL of resin. [Figure 4]FIG. 4. Experimental setup to investigate bacterial reduction by BacCap resin; 1. Reservoir containing bacterial suspension of E. coli, 104 Cfu / L, 2. Pump, 3. Column / cartridge containing instruction BacCap resin, 4. Fraction. [Diagram 5] FIG. 5 shows the kinetic results of bacterial removal on an ion exchanger coated only on the outside. [Figure 6] FIG. 6 shows the concentration of Pseudomonas aeruginosa over time under static conditions in the presence of instrAction BacCap resin. [Figure 7] FIG. 7 shows the bacteriostatic effect. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0044] Current status for manufacturing instrAction MetCap and BacCap resins Simplifying the manufacturing process, reducing waste disposal, and using ion exchange for softening. Expand your product range by combining exchange properties with known binding properties of metals or bacteria and to address the issue of perfluorosurfactants, which are becoming increasingly problematic in drinking water treatment. Produce an adsorption resin for adsorption. In addition, use an organic carrier, e.g. polystyrene. By expanding the product range to include various particle sizes and pore sizes, The availability of polystyrene is a major advantage for this application. It is a well-established commercial product.
[0045] The simplification of the manufacturing process using polystyrene resins reduces the need for desalting of the polymer hydrolysate. By the way, and in particular by the addition and drying of the carrier polymer for preparing the polymer solution. This is achieved by further process changes regarding
[0046] Surprisingly, the polymer solution was successfully transferred to the porous polystyrene particles without prior desalting. MetCap® and BacCap® resins were prepared by immobilization of Previous studies have investigated the deposition rate of polymers on porous supports and demonstrated that the immobilization rate was significantly dependent on the salt content of the polymer hydrolysate. This is surprising because
[0047] Adjustment of coating processes (e.g. multi-coating, Lodige ploughshares) By implementing new cleaning methods, we can avoid any shortcomings in product performance. This avoids the need for a complex and costly process step of desalting the polymer hydrolysate. Cut.
[0048] For these reasons, we decided to change the manufacturing process, especially to omit the desalination by membrane filtration. It can also be said that the deployment of organic support materials offers decisive advantages.
[0049] The polymer content is determined by batch calculations during polymerization. The results showed that ethylene glycol diglycidyl ether was used in the Lodige vacuum shovel dryer. Coating and pre-crosslinking with diethyl ether were performed using salt-free PVAm polymer solutions. Secondly, the salt contained in the polymer serves exactly the same function as that of the polymer used for post-crosslinking. During the preparation of the suspension, the silica gel carrier is partially dissolved by the sodium hydroxide solution. After being dissolved in water, all salts (silicates, formates, chlorides, etc.) were dissolved in water to form cross-linked pure cast iron. The organic material is washed away from the mold. The BacCap® T material thus obtained Alternatively, MetCap® T material is processed using desalted PVA polymer. This is the first improvement in the process, but it has a large This is a big surprise because, as evidenced by the data in the literature, A common assumption is that the high concentration of salt in the polymer solution requires volume, and therefore the bulk is simply The height prevents efficient and complete packing of the polymer into the particles. .
[0050] The second method is to mix commercially available strong or weak ion exchangers with antibacterial PVA polymers. It concerns coating with a rimar shell.
[0051] Commercially available ion exchangers, and in particular the cation exchangers used herein, are usually based on polymeric supports ( The acid group is covalently bonded to a polymer (e.g., polystyrene, acrylate, etc.). In the case of a weak ion exchanger, it is a carboxylic acid or a carboxylate, and in the case of a strong ion exchanger, it is They are sulfonic acids or sulfonates. Both types are used to soften drinking water.
[0052] It provides these ion exchangers with antibacterial properties without significantly reducing their softening ability. In order to achieve this, it is necessary to modify the acid groups in the particle pores, where most of the functional acid groups are present. Only the outer coating of the particles is required.
[0053] This target is unable to enter the pores of the ion exchanger particles due to its size and hydrodynamic radius. This is achieved by using the corresponding polymers that cannot be used for ion exchange. The pore size of commercially available ion exchangers is The size ranges from 20 nm to 100 nm. The thick polymer cannot penetrate into these pores.
[0054] In this procedure, in a preferred embodiment, the periphery of the particle as measured in the radial direction of the particle is More preferably, only 2-25% of the surface is coated as measured in the radial direction of the particle. When coating, only the outer 2-10% of the particle is coated. Most preferably, the outer 2-10% is coated, measured in the radial direction. When the particles are heated, only the outer 2-5% of the particles are coated.
[0055] Undoubtedly the majority of the ion-exchangeable groups are thus available for water softening.
[0056] Non-desalted polymers of corresponding size can also be used for this purpose, but this Not a requirement. Non-desalted polymers can be used, or coated with desalted polymers. be.
[0057] The amide groups of polyvinylamine are hydrolyzed with sodium hydroxide solution, followed by neutralization with hydrochloric acid. After this, the polymer is dissolved in about 15-25% by weight of sodium formate and sodium chloride. The polymer content of the aqueous solution is 9-13% by weight for non-desalted polymers. Equivalent.
[0058] The previous process involved a complex process of reverse osmosis to remove salt, resulting in a salt content of 2.5 The new process eliminates this complex and expensive desalting step. Therefore, the new process allows partial elimination of salt content between 2.5 and 15% by mass. It is preferable to use a polymer that has been thoroughly desalted. It is more preferable to use a polymer that has been thoroughly desalted. Most preferably, a desalting polymer is used. EXAMPLES
[0059] Example 1 1712 g of wet support material, Lewatit S1567 ion exchanger, was added to Lo The ion exchanger was then directly transferred to a Dige VT5 ploughshare mixer. Dry at 0°C for 60 min. The water loss was determined by measuring the mass of the dried ion exchanger. The loss in water is measured. 380 g of water is removed. The temperature of the product in the dryer is set at 10°C. The mixer is operated at 180 revolutions per minute. The product temperature in the mixing tank is kept at 10°C. When it reaches 225g of ion exchanger, undesalted polyvinylamine solution batch: PC1800 7 (polymer content 10%) was cooled to 10°C and ethylene glycol diglycidyl ether was added. Weigh 1g of EGDE [2224-15-9] into a container until the total volume is 350mL. Add deionized water until the mixture is completely dissolved. Place this mixture in a mixer within 10 minutes and mix for 1 hour at 10°C. The polymer adsorbate is then crosslinked at 80° C. and a reduced pressure of 50 mbar for 2 hours. The polymer-coated ion exchanger was then cooled to room temperature.
[0060] The particles are then transferred to a suitable suction filter and washed with the following solvents (BV=bed volume): 3BV 0.1M NaOH, 3BV deionized water, 3BV 0.2M HCl, 3BV water, 6BV 0.1M NaOH, 6BV deionized water. The product, BacCap, is wet with water. The resulting particles are
[0061] Example 2 3 L of Lewatit S 8227 from Lanxess on a porosity 3 frit The wet ion exchanger is then weighed out at 2270 g and washed with 15 L of deionized water. The ion exchanger is placed in a VT 5 vacuum shovel dryer manufactured by Odige. The jacket temperature Dry for 2 hours at 80°C, 30 mbar pressure and 57 rpm rotation speed. After drying, 915 g Place the dried ion exchanger back into the VT 5 vacuum shovel dryer. Set the jacket temperature to 4°C. Adjust the temperature of the product to below 20°C and add 600 mL of deionized water within 15 minutes. The mixture was pumped into the mixer by a peristaltic pump and the mixer was operated at a rotation speed of 180 rpm. The coating consisted of 227 g of polyvinylamine solution (10% polymer content) Weigh out PC18007 and 227g of deionized water into a container. Ethylene glycol diglycidyl ether (EGDGE) [2224-15-9 ]9. Weigh 20 g into a separate container. Add the crosslinker to the polymer solution and mix vigorously. Continued The mixture was then pumped into a Lodige mixer using a peristaltic pump within 5 minutes. Adjust the mixer speed to 240 rpm and keep the jacket temperature at 4°C. Mixing was then continued for 15 minutes at 240 rpm. The dryer jacket temperature was then increased to 80°C. Adjust and control the rotation speed to 120 rpm.
[0062] The particles are then cooled again to room temperature and subsequently transferred to a suitable suction filter and diluted with the following: Wash with solvent: 3BV 0.1M NaOH, 3BV deionized water, 3BV 0.1M HC 1, 6BV water. The product BacCap is obtained as water-wet granules.
[0063] Example 3 500 g of the carrier material was sulfonated polystyrene with a water absorption capacity of 1.35 mL / g. PRC 15035 (average pore size 450 Å, average particle size 500 μm) was used for L Direct intake into an Odige VT5 ploughshare mixer. Dryer product temperature Adjust the temperature to 10°C. Operate the mixer at 180 revolutions per minute. The product temperature in the mixing tank is Once 10°C has been reached, 225g of the unsalted polyvinylamine solution batch was cooled to 10°C: C16012 (polymer content 12%), 20g of ethylene glycol diglycidyl ether EGDGE CAS No. [2224-15-9], and 430g deionized water Weigh into a container. Place the mixture in the mixer within 10 minutes and mix for 1 hour at 10°C. The polymer adsorbent is then crosslinked at 65° C. The product is then cooled to room temperature. Transfer the particles to a suitable suction filter and wash with the following solvents: 3BV 1M NaOH, 3 BV deionized water, 3BV 2M HCl, 3BV water, 6BV 1M NaOH, 6BV deionized on water. 1297 g of product is obtained as water-wet granules. Anion Capacity (AIC): 4 71 μmol / g.
[0064] Example 4 Preparation of porous particles of crosslinked polymer with a particle size of 100 μm (batch: BV 1800 7) Description: First preparation of polymer adsorbent: 750 g of silica gel ( AGC Si-Tech Co. MS Gel D-200-100 Batch: 164M0 0711) is delivered directly to a Lodige VT5 ploughshare mixer. The product temperature is adjusted to 10°C. The mixer is operated at 180 revolutions per minute. Once the temperature reaches 10°C, add 1125g of the unsalted polyvinylamine solution batch: PC180 07 (polymer content 10%) was cooled to 10°C, weighed and placed in a container, and 23.2 g of ethylenediaminetetraacetate was added. Ethylene glycol diglycidyl ether (EGDGE) CAS No. [2224-15 -9] is added. The mixture is placed in a mixer within 10 minutes and mixed for 1 hour at 10°C. The polymer adsorbent is then dried at 80° C. and 50 mbar (approximately 2 hours). The coated silica gel was cooled to 10°C. For the second coating, the polymer solution was 750 g of PC18007 (polymer content 10%) was cooled to 10°C, weighed into a container, and Ethylene glycol diglycidyl ether (EGDGE) CAS No. [2224-15 15 g of 1000-9 was added. The polymer solution was poured into the mixing drum within 5 minutes. The adsorbent was mixed at 10°C for 30 minutes. In addition, the temperature in the Lodige mixer was increased to 10°C for 1 hour. The temperature was raised again to 65°C for a period of time. 3 L of deionized water was added to the polymer adsorbent. is used for crosslinking. Silica gel suspended in water and coated is heated at an automatic temperature control. Transfer to a 10 L glass reactor. Stir the suspension and heat to 80° C. Then add epichlorohydrin. Add 317g of hydrin CAS number [106-89-8] within 20 minutes, and the reaction The temperature in the reactor should not exceed 85°C. In addition, 211 g of 1,2-diaminoethane Add epichlorohydrin CAS [107-15-3] dropwise within 20 minutes. A second addition of 317 g of No. [106-89-8] was made within 20 minutes, followed by 21 Add 1g of 1,2-diaminoethane CAS No. [107-15-3] again. 317g of epichlorohydrin CAS No. [106-89-8] was added in the final step. The reaction mixture is then stirred at 85° C. for 1 hour. The reaction mixture is then cooled to 25° C. and stirred at 1500° C. 1 mL of 50% NaOH is added and the reaction mixture is stirred for 12 h. Transfer to a suitable suction filter and wash with the following solvents: 3BV 1M NaOH, 3BV desorb deionized water, 3BV 2M HCl, 3BV water, 6BV 1M NaOH, and 6BV deionized water On water.
[0065] The product is obtained as a moist filter cake.
[0066] Example 5 The adsorption resin prepared according to Example 1, Example 3, or Example 4 is dissolved in a solvent, e.g., DM F. Then, 110 mol % glycidyl-2,2,3,3,4,4,5,5- Octafluoropentyl ether (based on the amino groups of the starting resin, FIG. 2) was added to the resin by stirring. The suspension is stirred at 70°C for 12 hours. Wash with: 3BV DMF, 3BV n-heptane, 3BV 1M H in DMF Cl, 3BV 1M NaOH in DMF, and 3BV DMF. Again, 50% in DMF In the second reaction step, 110 mol % glycidyl-2,2,3, 3,4,4,4,5,5-Octafluoropentyl ether is added to this suspension again. The reaction mixture is stirred at 70°C for 12 hours. The adsorption resin is washed with the following solvents: To prepare: 3BV DMF, 3BV n-heptane, 3BV 1M HCl in DMF, 3BV 1 M NaOH in DMF, 3BV MeOH. Finally, the adsorption resin was dried under reduced pressure until constant mass. It may be dried at .
[0067] The structure of the adsorption resin is shown in Figure 1.
[0068] Example 6 The adsorption resin prepared in Example 5, activated carbon (100 angstroms, 45 μm), and Commercially available C-18 chromatography gel (Kromasil, C18, 100 Å) Each of the HPLC columns measuring 33.5×4 mm was filled with 10 μm of tetrahydrofuran (10 μm). The column is sealed and subjected to frontal analysis. For this analysis, 100 ppm perfluorooctanoic acid is added. A solution of methacrylic acid in water is prepared and pumped through the column until performance is lost. It is measured by UV spectroscopy at 100 nm.
[0069] The following table (Table 1) shows the adsorption capacity of perfluorooctanoic acid measured on the three adsorbents. is.
[0070] [Table 1]
[0071] As shown in Table 1, the adsorption capacity of perfluorooctanoic acid is phase (batch number ND 150201), it was about 3 to 4 times higher than that of activated carbon. Commercially available RP18 gel shows no adsorption of perfluorooctanoic acid.
[0072] The breakthrough curve of the frontal analysis is shown in FIG.
[0073] Example 7 Suspension of instrAction resin (BV 18009, prepared as in Example 3) in water Prepare the solution and add 100 mL of water to the bed volume (average bed dimensions: 6.3 x 9 cm). The cartridge is filled with a flow path in the direction of the flow.
[0074] Next, E. coli (10 4 ~10 5 The suspension of the 100-500 CFU / L is pumped at 100-500 mL / min. The pump pumps the cartridge at a stepwise increasing flow rate of (60~300BV / h) / h. The effluent was collected at each flow rate step after approximately 3-5 minutes and then analyzed using standard procedures. Check for residual bacteria.
[0075] The survey results are shown in Figure 5. No bacteria were detected in the effluent over the entire survey area. means that bacteria are completely removed at concentrations comparable to those found in drinking water.
[0076] Example 8 Regarding the activity against P. aeruginosa, the instrAction tree prepared in Example 3 was used. The lipids are examined as follows: 500 g of resin washed with tap water is dissolved in Pseudomonas aeruginosa in 10 mL tap water. Domonas aeruginosa 10 6 Incubate in a reaction vessel with the CFU suspension. Samples were taken after 3, 6, 12 and 24 hours and analyzed using standard methods. Pseudomonas aeruginosa was examined. The results are shown in Figure 6. After 3 hours of incubation, With just the incubation, the bacteria are no longer detectable.
[0077] Example 9 Water Filtration Bottle Commercially available water filtration bottles manufactured by Brita and BWT were used. and a mixture of the instrAction resin of the present invention prepared according to Example 3, and The bacterial growth rate was significantly reduced when compared to the original cartridges with silver added. Reproduction was compared.
[0078] For this purpose, we first isolated 8.3 × 10 5 cfu / L suspension 1 L was added to the cartridge, stored, and the eluted bacteria were examined after 3 weeks.
[0079] The survey results are shown in Figure 7.
[0080] As expected, some of the silver added to the cartridge was eluted, resulting in fine particles in the filtrate. The original cartridges from BWT and Brita were silver-filled to prevent bacterial growth. No bacteria can be detected in the cleaning medium. Similarly, cartridges containing 1,2-dichlorophenyl 1,3-dichlorophenyl 1,4-dichlorophenyl 1,5-dichlorophenyl 1,6-dichlorophenyl 1,7 ... It detects only very reduced numbers of bacteria, approaching the kingdom.
[0081] Thus, the bacteriostatic effect of the resin claimed in this application is demonstrated. There is no need to add any extra silver to the cartridge.
[0082] The filtration rate of the cartridge filled with the claimed mixture of resin and activated carbon is This is important because it is comparable to commercially available cartridges containing added silver.
Claims
1. 1. A method for producing antimicrobial coated particles, comprising: (a) a polyamine, a crosslinker, and a particulate porous organic support material or an inorganic support an aqueous suspension containing the material for coating the inorganic support material with the polyamine; feeding into a mixer at a temperature of 10° C. or less; and (b) removing water while crosslinking the organic polymer within the pores of the inorganic support material; The method includes:
2. The method of claim 1 , wherein steps a) and b) are repeated at least once.
3. 3. The method according to claim 1, wherein the crosslinking is carried out in a stirred reactor.
4. The method according to any one of claims 1 to 3, wherein the polyamine is used in a non-desalted state. 。
5. The method according to claims 1 to 4, wherein the organic polymer is polystyrene.
6. The organic polymer is a strong or weak anion exchanger, and only the outer surface The method according to claims 1 to 4, wherein the polymer is coated.
7. The organic polymer is selected from the group consisting of polystyrene, polymethacrylate, and polyacrylate. The method according to claims 1 to 4, wherein the compound is selected from the group consisting of
8. The polymer is an inorganic polymer selected from silica gel and hydroxyapatite. The method according to claims 1 to 4,
9. The method according to any one of claims 1 to 7, wherein the polyamine is a polyvinylamine. 。
10. A porous particle produced by the method according to any one of claims 1 to 9.
11. 11. The porous particle of claim 10 for removing bacteria from water, drinking water, or other aqueous solutions. Child use.
12. 11. The porous membrane of claim 10 for removing heavy metals from water, drinking water, or other aqueous solutions. Use of particles.
13. 11. The porous particles according to claim 10 for removing elemental acid anions and elemental acidous anions. Child use.
Citation Information
Patent Citations
Collection and recovery agent for surfactant
JP2009207994A
Adsorbent for organic fluoro-compound comprising cyclodextrin-supported polymer
US20150314266A1
Organic fluorine-based-compound adsorbent comprising cyclodextrin-supporting polymer
WO2014087838A1
Removal of bacteria from drinking water via filtration
WO2019025488A1